„És amikor eljön az est…”: (Borbély Szilárd: Berlin & Hamlet) - Papp, Máté (Studia Litteraria, 2016)
Szilárd Borbély’s Berlin & Hamlet may raise a number of questions about the subjectivity of postmodern text creation. Berlin has a special place in the ambivalent relationship between the literary tradition evoked by the poems and the author’s unexpressed intention. All of these broaden and narrow down the range of possible interpretations of this book. The streets, statues, museums of the place called ”Urbangod” stand as the crumbling sets of the declining European culture. Parallel with this, the tools of poetry seem to peel off the disappearing character of the poet, who represents an existence without a centre. The language of the poems is a mixture of sceptical and elegic tones, while the textual world is enigmatic, fragmented and it relativizes the allegorical speech – all these give way to a number of assumptions about the lyrical self which is revealed in poetical roles, and which, at times, exposes itself. A monological dialogue stems from the implications of the hiding lyrical self and the summoned spectre, in which the distance between the speakers and the addressees is insurmountable. This distance can be partially covered by an analysis, as the author, lost in the labirynth of sounds, can only fill the space between the texts by his own absence.